EVALUASI PROGRAM KURIKULUM MERDEKA DI KABUPATEN PONOROGO MENGGUNAKAN MODEL CIPP - Rengga Aprilia; Feby Eka Listinai; Mufarrihul Hazin (CV. ALIM'SPUBLISHING, 2024)
The curriculum is the key to the success of learning. Therefore, in order to achieve this success, it is necessary to conduct evaluations to improve and analyze the implementation readiness of the curriculum, to be used as consideration in making decisions. This research examines the implementation of the Merdeka curriculum. This study was conducted to assess and evaluate the implementation of the Merdeka curriculum program in Ponorogo Regency using the CIPP evaluation model (Context, Input, Process, and Product). Data sources were obtained from interviews conducted with the Head of the Elementary School Department in Ponorogo Regency. The interview results were then analyzed using qualitative descriptive analysis. The conclusion drawn from this research is that the implementation of the Merdeka curriculum program in Ponorogo is carried out well, although it is hindered by some obstacles such as internet networks that are not accessible in all areas.